Pengaruh Penyuluhan Pemeriksaan Payudara Sendiri (SADARI) dengan Media Leaflet Terhadap Pengetahuan Remaja Putri - Fitriani; Yuatati, Eva; Afriani, Berta (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2024)
Breast cancer cases in Indonesia were 58,256 cases or 16.7% of the total 348,809 breast cancer incidents reaching 42 cases per 100,000 population, with an average death rate of around 17 cases per 100,000 population. Research design with quasi experimental one group pre-test and post-test. The population in this study was 25. Samples taken (total sampling). A total of 25 samples. The results of the univariate analysis before counseling was given, the average student score was 5.76, standard deviation 1.128, while after counseling the average student score was 7.96. and standard deviation 1,013. Results of bivariate analysis, the average value of pre-test knowledge is 5.76, while the average value of post-test knowledge is 7.96. It can be seen that the increase in the average value between knowledge before and after being given counseling is 2.2. The results of the wilcoxon signed ranks test statistic showed a p value of 0.000. Conclusion there is an influence of counseling on the level of knowledge of adolescents about BSE